What drives forbearance - evidence from the ECB Comprehensive Assessment - Timotej Homar; Heinrich Kick; Carmelo Salleo (European Central Bank (ECB), 2015)
Forbearance is a practice of granting concessions to troubled borrowers, typically in the form of prolongation of maturity or refinancing of the loan. While economically useful in some circumstances, it can be used by banks in order to reduce the need for provisions and conceal potential losses. If forbearance is widespread in the banking system, it may result in systemic risk, increasing uncertainty about the quality of banks' assets and undermining trust in the banking sector's solvency. This paper provides the first empirical analysis of forbearance in Europe, using the adjustment of nonperforming exposures due to the AQR and the associated increase in required provisions as measures of forbearance. Our results highlight weak macro-economic conditions, lax bank supervision and individual bank weakness as the key factors.
Keywords: G21; G28; 330; asset quality review; forbearance; nonperforming loans; zombie lending